Bethel Church (Quincy, Ill.) Bulletin, undated [between 1924-1934] - (:unkn) unknown (My University, 1924)
Bethel Bulletin, undated [between 1924-1934]. Church bulletin for Bethel Church in Quincy, Illinois.
1 pdf document, 4 pages. Bethel Bulletin, undated [between 1924-1934]. Church bulletin for Bethel Church in Quincy, Illinois. Adele and Richard Carmichael: Series 2, Box 1, Folder 1, ephemera Bethel church years. MS/150/9 Valdosta State University Archives and Special Collections. Bethel Church Assembly of God (Quincy, Ill.)
Keywords: Bethel Church Assembly of God (Quincy, IL); Church bulletins; Quincy (Ill.); Carmichael, Richard, Rev., 1900-1960; Carmichael, Adele, Rev., 1902-2003; New Age ministers; Pentecostalism; Women evangelists; Evangelistic work; Church musicians; Clergy